The True Story of Christopher Columbus, Called the Great Admiral - Brooks, Elbridge S. (Elbridge Streeter), 1846-1902 (Salt Lake City, UT : Project Gutenberg, 2006)
"The True Story of Christopher Columbus, Called the Great Admiral" by Elbridge S. Brooks is a historical account written in the late 19th century. The work embarks on an engaging journey through the life of Christopher Columbus, detailing his ambition to discover a westward route to Asia, specifically to the riches of Cathay, ultimately leading to his unexpected discovery of the New World. The narrative serves to glorify Columbus's achievements and character, presenting him as a symbol of exploration and perseverance for young readers. The opening of the book introduces Columbus's early life as a boy filled with dreams of adventure in the beautiful city of Genoa. It captures his fascination with the sea, his desire to explore unknown lands, and how he became convinced that he could reach Asia by sailing westward. As the narrative unfolds, it details the skepticism he faced regarding his innovative ideas, highlights his determination to seek support from royals, and establishes the hardships he endured while pursuing his dreams. The story emphasizes his persistence and ingenuity, setting the stage for the dramatic voyages that would eventually change the course of history. (This is an automatically generated summary.)
Release date is 2006-02-15
Produced by Charles Keller and David Widger
Keywords: Columbus, Christopher, 1451-1506 -- Juvenile literature; Explorers -- Juvenile literature